Fluorine-induced dual defects in cobalt phosphide nanosheets enhance hydrogen evolution reaction activity - Xu, Kun (2020)
Introduction of defects in a controllable way is important to modulate the electronic structure of catalysts towards enhancement of electrocatalytic activity. Herein, we report that fluorine incorporation into cobalt phosphide alloy has a unique effect – it creates both F-anion doping and P vacancy, which results in nearly 15-fold enhancement in catalytic activity for hydrogen evolution reaction (HER) in neutral solution. The existence of dual defects in CoP is confirmed by extended X-ray absorption fine structure (EXAFS) curve fitting results and density functional theory calculation. We show that the dual-defect feature is beneficial to increasing the active site exposure, tuning the surface wettability and optimizing the electronic configuration of CoP for HER. Our fluorine based modulation protocol may be applicable to other metal alloy electrocatalysts towards more efficient energy conversion reactions.